UJI AKTIVITAS ANTELMINTIK INFUSA DAN EKSTRAK ETANOL DAUN PEPAYA JEPANG (Cnidoscolus aconitifolius) TERHADAP CACING GELANG BABI (Ascaris suum) SECARA IN VITRO - Asman Sadino; Dina Rosdiana; Anas Subarnas; Riza Apriani (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
Ascaris suum is a parasitic worm in pigs that is closely related to the worm in humans, A. lumbricoides. A literature search shows that A. suum can infect humans. Ascaris is thought to modulate host immune and inflammatory responses, which may lead to immune hyporesponsiveness during chronic infections. Treatment with anthelmintic drugs is considered to increase the risk of resistance. Thus, alternative medicines from natural ingredients are needed that are more effective and have minimal side effects, including Japanese papaya leaves (Cnidoscolus aconitifolius). This research aimed to analyze the anthelmintic activity of ethanol extract and Japanese papaya leaf infusion against A. suum worms and eggs in vitro. Testing was divided into 6 large groups, namely test group (extract and infusion concentrations of 3%, 6%, and 9%), comparison group (pyrantel pamoate 1% and piperazine citrate 2% for testing adult worms and mebendazole 0.25% for testing worm eggs), and control group (NaCl 0.9% and PGA 1%). The parameters looked at are the form of paralysis, death of adult worms, and the percent inhibition of worm eggs. The results of the research were the anthelmintic activity shown by Japanese papaya leaf extract (C.aconitifolius) against pig roundworms and their eggs at a concentration of 9% compared to test concentrations of 3% and 6%, pyrantel pamoate, piperazine citrate, and mebendazole. This research concludes that Japanese papaya (C.aconitifolius) leaf extract has anthelmintic activity against pork roundworms and their eggs.